THE INFLUENCE OF LIVE STREAMING STIMULI ON IMPULSE BUYING BEHAVIOR OF FASHION PRODUCTS AND USER STICKINESS ON SHOPEE AND TOKOPEDIA LIVE - Gorga Agustinus Pangihutan; Anna Amalyah Agus (Journal of Economic, Bussines and Accounting (COSTING), 2025)
The growth of e-commerce in Indonesia has driven the integration of live streaming as a dynamic marketing tool. This research explores how live streaming stimuli affect both impulse buying behavior and user engagement, with perceived hedonic value acting as a mediating factor. Employing a quantitative method through Structural Equation Modeling (SEM) and surveying 300 participants, the study reveals that live streaming stimuli have a significant impact on triggering impulsive purchases and fostering user interaction. Additionally, perceived hedonic value plays a key role in strengthening consumer engagement with e-commerce platforms. The findings offer valuable insights for marketers and online platforms to develop more impactful live streaming strategies for product promotion.